IMPLEMENTASI NILAI-NILAI AL-QUR’AN DALAM REGULASI DI PKBM IBNU TAIMIYYAH BUKITTINGGI PERSPEKTIF TAFSIR MAQASHIDI - Siska Mona Widia; Muhammad Taufiq (CV. Adiba Aisha Amira, 2025)
Community Learning Activity Center Ibnu Taimiyyah Bukittinggi is an educational foundation established since 2019 in Bukittinggi, West Sumatra, which aims to produce generation of qur'ani and become da'wah educational institution. To achieve this goal, policy was formed that adopted Qur'anic values. However, some regulation makers don’t understand the science of tafsir to interpretation the surah for school regulations. This study examines process of developing regulations that integrate Qur'anic values, the verses used in making regulations, and perspective of tafsir maqasidhi on the understanding of the parties making regulations at PKBM Ibnu Taimiyyah Bukittinggi. This study aims to analyze the suitability of tafsir maqasidhi with regulations at PKBM Ibnu Taimiyyah bukittinggi. The methodology is empirical research, with qualitative approach, which is based on primary data of observations or interviews. The study findings indicate that the rules made at PKBM Ibnu Taimiyyah refer to surah al-'Asr, surah al-Isra verse 32, and surah al- Muzzammil verse 4. All rules based on these surahs are in accordance with the meaning of the interpretation of each surah and in accordance with maqashidi because there are still some parties who make regulations understand the science of tafsir even though others don’t understand the science of tafsir interpretation